Deciphering the absorption profile and interaction of multi-components of Zhi-Zi-Da-Huang decoction based on in vitro–in silico–in vivo integrated strategy. (3rd July 2019) - Hu, Qing; Li, Xixi; Shi, Qingshui; Yang, Gongjun; Feng, Fang
Abstract: Zhi-Zi-Da-Huang decoction (ZZDHD) has been acknowledged with striking therapeutic effects for hepatobiliary disorders in the history of China. As decoctions are usually administrated orally, intestinal absorption, the prerequisite task of exerting therapeutic effects, is of utmost significance for screening potential active compounds and understanding the mechanism of drug action. In this work, an in vitro – in silico – in vivo strategy based on HPLC-DAD-ESI-TOF/MS was adopted for precisely profiling the intestinal absorption of ZZDHD, which integrated information obtained from rat everted gut sac model, octanol–water partition model, in silico prediction and in vivo experimental data. Besides, 34 main absorbed ingredients were selected as chemical markers to investigate the compatible interaction of the decoction on absorption level using rat everted gut sac experiment. In total, 106 compounds of ZZDHD were speculated as potential absorptive. Among them, 90 constituents predicted absorbable in at least two experimental models were finally recognized as intestinal absorbable ingredients. In addition, the absorption level of iridoids, terpenoids and flavonoid glycosides were found improved and the absorption of catechins and anthraquinones were inhibited after prescription compatibility. Taken together, this study presents a reliable strategy for evaluating intestinal absorption of herbal medicines and offers a reference for the rationality of herbal compatibility and the modernization of traditional Chinese medicine (TCM).